2016
DOI: 10.1123/jsm.2016-0032
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Communicating Vessels Framework to CSR Value Co-creation: Empirical Evidence From Professional Team Sport Organizations

Abstract: Despite the increasing number and significance of charitable foundations in various business sectors, their role in cocreating corporate social responsibility (CSR) value remains unclear. This paper identifies CSR value cocreation in professional team sport organizations (PTSOs) and answers three key research questions: (a) Why have PTSOs developed charitable foundations as their means toward CSR value cocreation? (b) What CSR-related resources do PTSOs and their charitable foundations integrate? and (c) How d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 65 publications
2
57
0
1
Order By: Relevance
“…According to the reciprocity principle, it is expected the trustee will not abuse the trustor as they give direct or indirect benefits to one another (Lévi-Strauss, 1969;Molm et al, 2007). For example, the 'parent' team supports its charitable foundation with financial and/or contributions-in-kind with the view that the latter will juxtapose a positive image in the community where the former exists and operates (Anagnostopoulos et al, 2017;Kolyperas et al, 2016).…”
Section: Reciprocal Trust Relationship and Social Exchange Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…According to the reciprocity principle, it is expected the trustee will not abuse the trustor as they give direct or indirect benefits to one another (Lévi-Strauss, 1969;Molm et al, 2007). For example, the 'parent' team supports its charitable foundation with financial and/or contributions-in-kind with the view that the latter will juxtapose a positive image in the community where the former exists and operates (Anagnostopoulos et al, 2017;Kolyperas et al, 2016).…”
Section: Reciprocal Trust Relationship and Social Exchange Theorymentioning
confidence: 99%
“…As previous research has shown (e.g., Anagnostopoulos et al, 2017;Kolyperas et al, 2016), foundation executives/CEOs are trying to secure as large and as consistent a buy-in as possible from the board members affiliated with the 'parent' team in exchange for contributing towards the latter's business-related objectives.…”
Section: 'Exchanging Currencies' For Trust Buildingmentioning
confidence: 99%
See 2 more Smart Citations
“…The two most prominent of these are generally: to maintain a high level of on-field performance and, to maximise off-field commercial business operations in the pursuit of revenue gains. For the latter, the concept of corporate social responsibility has started playing an increasingly important role (Breitbarth et al, 2015;Kolyperas et al, 2016). It is widely acknowledged in academia that these objectives are linked yet there is no clear consensus as to which is the cause and effect.…”
Section: Introductionmentioning
confidence: 99%